MAINTAINING THE SELF-EXISTENCE THROUGH SHORT STORY â€œJALAN SUMUR MATIâ€ - Wahyuni, Dessy; Maulina, Yeni (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2020)
Riau is a wealthy region where physical development appears everywhere. However, many people are marginalized and neglected by this development. Due to this fact, most Riau Malay people tend to have negative prejudice and not accept the presence of foreign immigrants, including Indonesian Chinese. However, Olyrinson can blend in with the local community through his work, which often raises topics about humanity and his real-life. Using a three-dimensional framework of Fairclough (1989; 1992a; 1992b; 1995a; and 1995b), this study critically explores the various efforts made by Olyrinson in the short story "Jalan Sumur Mati" to defend his existence by changing prejudices. In this case, the author analyzes relevant texts and explores dialectical relationships between literary works and other social practice elements, which will be presented through textual analysis, discourse practice, and social practice.